PENANGGULANGAN WABAH PENYAKIT MENURUT HADIS NABI SAW.: PEMADUAN AGAMA DAN SAINS SEBAGAI PROTEKSI DAN PENGOBATAN TERHADAP PANDEMI COVID-19 - Fatkhan Ansori (Jurnal Studi Hadis Nusantara, 2022)
This studies became driven through the outbreak of the Covid-19 Pandemic (Coronavirus disease 2019), Covid-19 is a sickness outbreak that can be deadly for its sufferers. The emergence of the covid-19 disease outbreak has indeed caught the attention of many human beings, they argue that the covid-19 ailment outbreak is a sickness that God has given to his servants, even though this isn't always real. The writer of Covid-19 is human beings themselves who act without considering the consequences. Which until mid-2020 has greater than a hundred ninety nations affected by this ailment outbreak and hundreds of thousands of humans have been inflamed with this virus, and claimed many lives humans round the arena. In Islam, a plague disease outbreak like this befell during the time of the Prophet Muhammad, the motion taken via Muslims at that point changed into to quarantine the area, with the aid of now not going out or coming from and to regions that have been being laid low with a sickness outbreak. In faith there are already instructions on the way to deal with disease, as well as a way to shield yourself and on the same time wreck the chain of spreading the virus, but those methods aren't understood via most of the people of people on this international. those ways begin from introspection with the aid of staying faraway from sickness outbreaks, continually praying to the khaliq, trusting in Allah, retaining private hygiene and the encircling environment, consuming halal food and drinks. This take a look at concludes that during religion there are ways to guard oneself from numerous sickness outbreaks.